2018
DOI: 10.3847/1538-4357/aad8bd
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Photoionized Turbulent Material in the Circumgalactic Medium

Abstract: The circumgalactic medium (CGM) of nearby star-forming galaxies shows clear indications of O VI absorption accompanied by little to no detectable N V absorption. This unusual spectral signature, accompanied by highly non-uniform absorption from lower ionization state species, indicates that the CGM must be viewed as a dynamic, multiphase medium, such as occurs in the presence of turbulence. Motivated by previous isotropic turbulent simulations, we carry out chemodynamical simulations of stratified media in a N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 155 publications
(188 reference statements)
1
9
0
Order By: Relevance
“…The critical velocity dispersion implied by the Voit (2018) model is broadly consistent with the findings of Gaspari et al (2013) for numerical simulations that drive turbulence, as well as with the observed velocity dispersions of galaxy-cluster cores that appear to be precipitating (Gaspari et al 2018). The turbulence cannot be much greater without either damping the perturbations through mixing with the ambient gas or overheating the ambient medium through turbulent dissipation (Gaspari et al 2013(Gaspari et al , 2017Banerjee & Sharma 2014;Buie et al 2018Buie et al , 2020. Around a galaxy like the Milky Way, the predicted one-dimensional velocity dispersion of hot gas in a precipitating CGM is therefore σ t ≈ 50-70 km s −1 .…”
Section: The Global Precipitation Limitsupporting
confidence: 74%
“…The critical velocity dispersion implied by the Voit (2018) model is broadly consistent with the findings of Gaspari et al (2013) for numerical simulations that drive turbulence, as well as with the observed velocity dispersions of galaxy-cluster cores that appear to be precipitating (Gaspari et al 2018). The turbulence cannot be much greater without either damping the perturbations through mixing with the ambient gas or overheating the ambient medium through turbulent dissipation (Gaspari et al 2013(Gaspari et al , 2017Banerjee & Sharma 2014;Buie et al 2018Buie et al , 2020. Around a galaxy like the Milky Way, the predicted one-dimensional velocity dispersion of hot gas in a precipitating CGM is therefore σ t ≈ 50-70 km s −1 .…”
Section: The Global Precipitation Limitsupporting
confidence: 74%
“…To this end, we can turn again to the example presented in Figure 1. Gray et al (2015); Gray & Scannapieco (2016); Buie et al (2018) showed that at low amounts of turbulence, σ 3D 10 km s −1 (top panel), MAIHEM mass fractions agree well with the pure photoionization case computed with CLOUDY (Ferland et al 2013).…”
Section: Application To Cos-halos Datamentioning
confidence: 52%
“…A key result of this analysis is that turbulence as included in these models promotes the density and temperature gradients needed to sustain both low, intermediate, and high ions simultaneously (Buie et al 2018). We see, however, that the MAI-HEM model does not provide a perfect description of the data for intermediate and high ions.…”
Section: Application To Cos-halos Datamentioning
confidence: 87%
See 1 more Smart Citation
“…Integral field unit (IFU) observations would be particularly useful, as the marked increases and decreases in brightness over the course of an oscillation would be correlated with the relative blueshifts and redshifts that track the compression and expansion velocities. No such correlations are expected for a turbulent multiphase environment, such as the ISM (and perhaps even the CGM; see Buie et al 2018). Computations of synthetic IFU observations for this signature APPENDIX A. LINEARIZED SOLUTIONS TO THE EQUATIONS OF NON-ADIABATIC HYDRODYNAMICS Here we linearize the equations of gas dynamics to derive the dispersion relation in equation (5), as well as the analytic solutions quoted in equation (11).…”
Section: Discussionmentioning
confidence: 99%